Karakteristik Perempuan Pedagang Buah di Pasar Tradisional Bahu Kecamatan Malalayang Kota Manado - Wandik, Piko; Manginsela, Elsje Pauline; Maweikere, Audrey Julia Maria (Sam Ratulangi University, 2024)
This study aims to determine and analyze the characteristics of women fruit traders in Traditional Market Bahu, Malalayang District, Manado City, North Sulawesi. The research used descriptive analysis method with more descriptions from the results of interviews and documentation. The data that has been collected is described and studied qualitatively and described in tabular form and explained descriptively. The results stated that female fruit traders in Bahu Traditional Market have age characteristics with a range of 18 years to more than 50 years, most respondents have a high school education level and most have a number of dependents of 1 person to 4 people, most have been trading for 6 years to 10 years, all fruit traders are married, have the right to ownership of the stall, with trading activities lasting 13 hours, traders sell several types of fruit such as mangosteen, banana, papaya, langsa, and the capital spent ranges from IDR1,000,000 to more than IDR6,000,000 and the respondent with the smallest profit was IDR1,190,000 and the largest was IDR6,842,000.